Take Control of Your Digital Storage, 2nd Edition - Carlson, Jeff (Take Control Books, 2020)
The Mac user's guide to mass storage Version 2.1, updated September 14, 2020 This book demystifies storage on the Mac, from mechanical hard drives to solid-state disks, and covering topics such as network-attached storage (NAS), cloud storage, repairing and managing disks, encryption, filesystems (including APFS), and managing data. As the amount of data we store continues to grow, figuring out where to put it and how to access it becomes more complicated. It's not just that we need to find space for our increasingly large collections of photos, videos, music, and apps-we want it to be available whenever we need it, and be sure that it's safe from hackers and thieves. Every Mac includes internal storage in the form of a hard drive, SSD, or Fusion drive. But you may also have one or more external devices (such as hard drives, flash drives, SD cards, or RAID devices), not to mention network-attached storage (NAS) devices or cloud storage (like Dropbox or iCloud Drive). Making sense of all your options, managing your stored data, choosing new devices or services when you're running out of space, or even just figuring out what's where can drive anyone to distraction. Fortunately, Jeff Carlson has a book with all the answers! After decades of working with Macs and accumulating massive collections of photos and videos, Jeff has pulled together a wide-ranging book about Mac storage that contains just the help you're looking for. Among many other topics, this book covers: How to choose a new (internal or external) hard drive, SSD, or hybrid drive Determining how much storage space you need What you need to know about APFS, Apple's new filesystem How to use APFS snapshots (a.k.a. Time Machine local snapshots) Formatting and partitioning disks using Disk Utility How to repair a misbehaving disk RAIDs: what they are and how different types compare How to tell when a hard drive is about to fail, and what to do about it What to do with a hard drive when it has outlived its usefulness When to use a flash drive or SD card How to create and use disk images Deciding among local, network, and cloud storage for various types of files What a personal cloud is and why you might consider using one Strategies for freeing up extra disk space NAS devices get special coverage, including: Why you might want a NAS How to choose a NAS-and when it's a better idea than an external hard drive Using a NAS with your Mac for a wide variety of purposes Special considerations whe...